Linking Agusan River access with Butuan residents' place attachment guide towards sociable riverfront - Oribiana, Katlyn Fei D.; Juanga, Jean Marie V. (2020)
The Agusan River is physically connected to Butuan City and it has been a big part of the city?s heritage for hundreds of years, yet few people seem to be attached to the river. This study tackles the place attachment of Butuan residents to Agusan River and what development could be done to encourage visitors. Surveys and interviews were used as instruments to gather data regarding place attachment, river access, activities, frequency and purpose of visits to destinations along the Agusan River. Surveys were purposively given out to 397 residents all throughout the city, while interviews were conducted with individuals specialized in architecture, engineering, tourism, and barangay management. Attendants of different sites located by the river were also interviewed. Majority (55%) of the survey respondents do not intentionally visit the river frequently, and interviews with experts confIsidoro R. Malaque IIIed this. Yet, analysis show that residents have high attachment towards Agusan River. It was analyzed that place attachment is negatively correlated to indirect and incidental visual accesses, while positively correlated to water interaction and destination visitation. Five riverside destinations were analyzed using the Strengths- Weaknesses-Opportunities-Threats Analysis to avoid threats and to incorporate positive traits in developing a public space that could boost place attachment. A criteria was created to select the new space?s location. The space was conceptualized based on the Great Place Theory and on what features and traits locals and experts desire. Issues found from the surveys and interviews were also considered. Through this development, different activities involving the three types of river access (touch, above, and see the water) may be generated. By making such activities available, locals would be encouraged to intentionally view and visit the river more frequently, therefore increasing their place attachment; having high place attachment could then engage non-locals to visit and appreciate the site as well.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2020